Penerapan Activity-Based Costing Pada Bengkel Las dan Konstruksi “ Artomoro ” Pekalongan - Akhmad Pujiono; Djauhar Edi P (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
Activity-Based Costing (ABC) is an accounting method that can be used to find the total cost of activities required to make a product. This study uses a descriptive qualitative method and aims to help SMEs welding and construction workshops